The social status of vocational education and training in Switzerland - Thomas Bolli; Ladina Rageth; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2019)
This paper analyses how the social status of vocational education and training (VET) in Switzerland has changed over time and how it differs across population groups. The applied measure for the social status of VET compares the cognitive abilities (measured by PISA scores) of prospective students in a VET programme to those in an academic baccalaureate programme. The results suggest that the social status of VET has remained constant between 2000 and 2012. The social status of VET is higher for women than for men, in rural than in urban areas, and for students with a parent born in Switzerland than for those with immigrant parents. In contrast, the social status of VET is independent of parents' education. Surprisingly, we find that the social status of VET is higher in the French- and Italian-speaking parts of Switzerland than in the German-speaking one. The reason is that prospective baccalaureate students have higher average abilities in the German part, while prospective VET students have about the same abilities in the German and French parts.
Keywords: 330; social status; education programmes; vocational education and training; apprenticeship; educational choices